2017
DOI: 10.1111/acer.13443
|View full text |Cite
|
Sign up to set email alerts
|

Decisions to Attend and Drink at Party Events: The Effects of Incentives and Disincentives and Lifetime Alcohol and Antisocial Problems

Abstract: Background Alcohol use disorders are associated with patterns of impulsive / risky decision making on behavioral economic decision tasks, but little is known about the factors affecting drinking-related decisions. Methods The effects of incentives and disincentives to attend and drink at hypothetical alcohol-related party events as a function of lifetime (LT) alcohol and antisocial problems were examined in a sample of 434 young adults who varied widely in LT alcohol and antisocial problems. Results Modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 38 publications
4
54
0
Order By: Relevance
“…Furthermore, in a study of drinking decisions in those with AUDs, high levels of comorbid AP symptoms were associated with higher rates of decisions to attend riskier drinking events (i.e. events associated with increased probability of negative outcomes), suggesting a greater insensitivity to aversive consequences compared to healthy controls (Finn, Gerst, Lake, & Bogg, in press). Studying discounting of delayed losses in individuals with AUDs and comorbid AP is particularly important given that, in cases of prolonged or habitual alcohol abuse, individuals' choices to continue drinking reflect, in part, a preference to avoid smaller immediate negative events (such as withdrawal, stress) in favor of long-term (delayed) negative consequences, such as serious health problems, divorce, and legal consequences (Madden & Bickel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a study of drinking decisions in those with AUDs, high levels of comorbid AP symptoms were associated with higher rates of decisions to attend riskier drinking events (i.e. events associated with increased probability of negative outcomes), suggesting a greater insensitivity to aversive consequences compared to healthy controls (Finn, Gerst, Lake, & Bogg, in press). Studying discounting of delayed losses in individuals with AUDs and comorbid AP is particularly important given that, in cases of prolonged or habitual alcohol abuse, individuals' choices to continue drinking reflect, in part, a preference to avoid smaller immediate negative events (such as withdrawal, stress) in favor of long-term (delayed) negative consequences, such as serious health problems, divorce, and legal consequences (Madden & Bickel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In regards to alcohol, risky drinking decisions may result in part because the party music may highlight the rewarding aspects of drinking/partying and at the same time reduce the possibility of considering the potential negative consequences of drinking, which would result in an increased likelihood to decide to drink without regard to potential risk. Finn and colleagues have found that alcohol party incentives can increase how much alcohol young adults decide to consume and their likelihood of deciding to attend the alcohol party events regardless of the negative consequences (Finn et al, 2017). Party music may have therefore contributed to the particular domain-specific effect found in the current study by specifically highlighting the positive aspects of drinking.…”
Section: Discussionmentioning
confidence: 66%
“…Young (or emerging) adults show a higher prevalence of substance use, heavy drinking, and binge drinking than any other age group (Chen & Kandel, 1995;Grant et al, 2004;White & Jackson, 2004). A key feature of the vulnerability associated with substance use disorders, including alcohol use disorder (Bickel & Marsch, 2001;Finn, Gerst, Lake, & Bogg, 2017;Garavan & Stout, 2005) is the propensity to make risky decisions, especially in emerging adults (Baer, 2002;Bernheim et al, 2012;Jackson, Sher, & Park, 2005). Emerging adulthood is characterized by instability in the social environment (Arnett, 2000) that leads to exploration of novel social bonding possibilities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations